Older is worse? Elderly patients who underwent gastrectomy: A single-center study - ERGENÇ, MUHAMMER (My University, 2023)
Aim:Gastric cancer is common cancer, and its incidence remains relatively high in elderly patients with increasing life expectancy. However, few studies have examined the clinical and prognostic characteristics of elderly gastric cancer patients undergoing gastrectomy. This study aimed to evaluate the clinical and prognostic features of elderly gastrectomy patients.Materials and methods:Patients over 65 years of age who underwent gastric cancer surgery at Marmara University were retrospectively analyzed. The patients\" demographics, American Society of Anesthesiologists scores, prognostic nutritional index (PNI), complications, intensive care unit duration, and length of stay were examined. The patients were divided into two groups: young-old (65-74 years old) and old-old (≥ 75 years old). Two groups were compared in terms of postoperative outcomes and overall survival.Results:Two hundred sixty-three patients were analyzed. The mean age was 79 years, and the female to male ratio was 85/178. Reoperation rates and hospital mortality were significantly higher in the old-old group (p=0.001 and p=0.01, respectively). The hospital stay was significantly longer in the old-old group (5.8 vs. 7.8 days, p= 0.02). Complications were significantly higher in the group with a PNI < 40 (49% vs. 23%, p=0.005). There was a significant difference between the two groups regarding 5-year overall survival (33% vs. 55%, p= 0.002).Conclusions:Gastrectomy can be performed on the elderly. However, an increase in complications and in-hospital mortality is recognized over 75. These problems should be considered in this old-age group.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; Cerrahi; Surgery